محاضرات في منهجية وتقنيات البحث - بوجمعة, نقبيل (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2024)
إن الحاجةالىالبحوثوالدراساتالعلميةفيازديادمطرد، لا تعرفالوقوفعند مستوى معين وذلك لصلتهاوارتباطها بمستجداتالحياةوتحدياتها، التي لا تعرف الركود، ولغرض مواكبة ما يحصل في الحياة من تطوروتغير لا بد من الاستمرارفيالبحثالعلميفي المجالات المختلفة،فالحاجةالىالبحثالعلميقائمةما دامتالحياة تشهد سباقامحموما فيالحصول علىأكبرقدرممكن من المعرفةالعلميةفي المجالات العلمية المختلفة، لذلك يعد البحث العلمي وما يتصل به من إجراءات وأدوات ومناهج من المتطلباتالأساسية في الحياة، ولذلكحظي باهتمام كبيرمن دول العالم،وتجسد هذا الاهتمام بالبحثالعلميفيما توليه المؤسساتالأكاديمية ومراكز البحوث من أهمية الأساليب البحث العلمي وتأهيل الباحثين للقيام بالبحوث العلمية بطريقة تضمن الدقة وتحقق أغراض العلم وأهدافه التي يسعى إلى بلوغها. وعلى هذا الأساسجاءت المطبوعةلتسليط الضوء علىالأسسالمنهجية في البحث وتقديمها الى طلبة علم النفس العيادي من خلالالإشارة الى نقاط هامة منها: العلم و البحث العلمي أهم المفاهيم أساسية له، أهداف البحث العلمي، أنواع البحوث العلمية و مناهجها، الفرق بين المنهج و المناهج، خصائص البحث العلمي،المتغيرات، مراحل البحث العلمي وخطواته، مشكلة البحث وصياغتها، مصطلحات و حدود البحث، أهمية الدراسة و أهدافها، فروض البحث، الفروض،.... The need for scientificresearch and studiesisconstantlyincreasing and does not know how to stop at a certain level due to its relevance and connection to the developments and challenges of life, whichdoes not know stagnation. In order to keep up with the development and change thatis happening in life, itisnecessary to continue scientificresearch in variousfields. The need for Scientific researchexists as long as life witnesses a feverish race in obtaining the greatest possible amount of scientificknowledge in variousscientificfields. Therefore, scientificresearch and the procedures, tools and approachesrelated to it are among the basic requirements in life, and thereforeit has receivedgreat attention from countries around the world, and thisisembodied. Paying attention to scientificresearch in the importance thatacademic institutions and researchcentersattach to scientificresearchmethods and qualifyingresearchers to carry out scientificresearch in a waythatensuresaccuracy and achieves the purposes and goals of science thatitseeks to achieve. On this basis, the publication came to shed light on the methodologicalfoundations of research and presentthem to students of clinicalpsychology by pointing out important points, including: science andscientificresearch, itsmost important and basic concepts, the goals of scientificresearch, types of scientificresearch and theirmethods, the differencebetweenmethod and methods. Characteristics of scientificresearch, variables, stages and steps of scientificresearch, the researchproblem and its formulation, terms and limits of the research, the importance of the study and its objectives, researchhypotheses, hypotheses,...